Separación e identificación de péptidos bioactivos liberados por bacterias lácticas - González Olivares, Luis Guillermo (Universidad Autónoma Metropolitana, 2011)
In this thesis peptides with biological activity have been separated and identified, mainly peptides with antihypertensive activity in commercial fermented milk with Streptococcus thermophilus and Lactobacillus acidophilus, during refrigerated storage. This thesis is structured in three parts. In the first part analysis of soluble peptides determination by Lowry technique was made, this in order to 1) determine the effect of time lapse of commercial fermented milk on the amount of soluble peptides found and 2) to standardize the amount of protein for further analysis. It was determined that no matter the time of preparation of fermented milk, the concentration of peptides followed a pattern of accumulation and formation, there was a growing trend of accumulation until day 10, which reached a maximum and remained constant until the end of the study. With these results, it was possible to standardize the amount of protein for further analysis. In a second part, the formation of peptides by special electrophoresis for peptides and denaturing electrophoresis were performed. In the denaturing electrophoresis the changes in protein concentration of milk, mainly - lactalbumin